Кримінально-процесуальні гарантії, їх види та місце інституту відводу, самовідводу у їх структурі - Денісова, Г.; Denisova, G. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2014)
Визначено поняття та суть кримінально-процесуальних гарантій, здійснено їх науково-обгрунтовану класифікацію. З'ясовано функціональну спрямованість іституту відведення та самовідводу посадових осіб, які ведуть кримінальне провадження. Окреслено місце і значення інституту відводу та самовідводу посадових осіб, які ведуть кримінальне провадження, у структурі кримінально-процесуальних гарантій. Процесуальні значення інституту відводу та самовідводу полягає в тому, що він одночасно є гарантією прав особистості, адже створює можливість усунути на законних підставах таку посадову особу, яка проявляє необ'єктивність. Такий правогарантуючий ефект інституту відводу та самовідводу дозволяє також його визнати і гарантією правосуддя. In modern conditions of reforming the criminal procedure implementation of criminal procedural guarantees by applying the institute rejection and self-rejection of officials leading the criminal proceedings has acquired special urgency. The concept and essence of criminal procedural guarantees is defined. Scientists judgments on the definition and scope of the criminal procedural guarantees are analyzed. The basic provisions are considered. Scientifically based classification of criminal procedural guarantees is carried out. The significance of criminal procedural guarantees in criminal proceedings assignments, including the protection of the individual, society and the state from criminal offenses, protection of rights, freedoms and legitimate interests of the criminal proceedings is defined. The functional orientation of rejection and self-rejection of officials leading the criminal proceedings institute is clarified. The place and importance of the institute rejection and self-rejection of officials leading the criminal proceedings is outlined in the structure of the criminal procedural guarantees. Procedural importance of the institute rejection and self-rejection of officials leading the criminal proceedings is at the same time in fact that it is a guarantee of individual rights, which protects their legitimate interests as it creates an opportunity to eliminate lawfully such an officer, who shows subjectivity personal interest in the decision of the criminal proceedings. Reality of access to justice will depend on the basis of this. Such lawguaranted effect of Institute of rejection and self-rejection also allows it to recognize as guarantee of justice.
Criminal Procedural Guarantees, their Types and Place of the Institution Rejection and Self-rejection in that Structure.
Keywords: кримінально-процесусальние гарантії; відвід; самовідвід; суддя; суд; прокурор; слідчий; кримінальне провадження; criminal procedural guarantees; challenged recuse; judge; court; prosecutor; investigator; criminal proceedings